1996
DOI: 10.1080/00140139608964474
|View full text |Cite
|
Sign up to set email alerts
|

Trust in automation. Part II. Experimental studies of trust and human intervention in a process control simulation

Abstract: Two experiments are reported which examined operators' trust in and use of the automation in a simulated supervisory process control task. Tests of the integrated model of human trust in machines proposed by Muir (1994) showed that models of interpersonal trust capture some important aspects of the nature and dynamics of human-machine trust. Results showed that operators' subjective ratings of trust in the automation were based mainly upon their perception of its competence. Trust was significantly reduced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
553
4
9

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 769 publications
(588 citation statements)
references
References 6 publications
22
553
4
9
Order By: Relevance
“…Consistent across different levels of automation, inappropriate levels of trust lead to extended reaction times or poorer reaction quality in hazardous situations (Abe, Itoh, & Tanaka, 2002;McGuirl & Sarter, 2006;Parasuraman & Riley, 1997). The causal mechanism could lie in participants' monitoring strategy: Muir and Moray (1996) as well as Bagheri and Jamieson (2004) found a decrease in monitoring with increasing trust. Hergeth et al (2016) also reported a negative correlation between participant's trust in automation and the extent of monitoring of a highly automated driving system during the engagement with an NDRT.…”
Section: The Role Of Trust In Automated Drivingmentioning
confidence: 98%
See 2 more Smart Citations
“…Consistent across different levels of automation, inappropriate levels of trust lead to extended reaction times or poorer reaction quality in hazardous situations (Abe, Itoh, & Tanaka, 2002;McGuirl & Sarter, 2006;Parasuraman & Riley, 1997). The causal mechanism could lie in participants' monitoring strategy: Muir and Moray (1996) as well as Bagheri and Jamieson (2004) found a decrease in monitoring with increasing trust. Hergeth et al (2016) also reported a negative correlation between participant's trust in automation and the extent of monitoring of a highly automated driving system during the engagement with an NDRT.…”
Section: The Role Of Trust In Automated Drivingmentioning
confidence: 98%
“…However, these claimed benefits may only occur if automated vehicles are successfully implemented into road traffic and trust in this technology is a vital precondition for this. Ghazizadeh, Lee, and Boyle (2012) stated in their Automation Acceptance Model that trust is a crucial contributor to an individual's acceptability of automation technology and several previous studies have empirically shown that trust is a key determinant for reliance on automated systems (Bailey & Scerbo, 2007;Muir & Moray, 1996), adoption of automation (Gefen, Karahanna, & Straub, 2003;Lee & Moray, 1994), and the intention to use autonomous vehicles (Choi & Ji, 2015). In other words, operators tend to use automation that they trust while rejecting automation that they do not (Pop, Shrewsbury, & Durso, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiment therefore gathered data on real world use of automation in contrast to much of the literature in the area which tends to use artificial simulations and/or non-expert participants (e.g. Lee & Moray, 1994;Sauer, Nickel & Wastell, 2013;Röttger, Bali, & Manzey, 2009;Endsley & Kaber, 1999;Bagheri & Jamieson, 2004;Beck, Dzindolet, & Pierce, 2007;Muir & Moray, 1996;Johnson et al, 2002;Meyer, Feinshreiber, & Parmet, 2003). Other studies which did use real world systems and expert operators have typically been more exploratory (e.g.…”
Section: Effects Of Automationmentioning
confidence: 99%
“…This has analogies with the issues of user trust in technology in general, and data in particular. Muir & Moray (1996) have demonstrated the strong positive relationship between trust in automation and automation use stating "operators used automation they trusted and rejected automation they distrusted". This is likely to apply in the context of GI data -in this case the perceived quality of the data is likely to have an impact on the extent to which it is trusted.…”
Section: Data Quality Language Quantity and Detailmentioning
confidence: 99%